Оценка фазового состава электролитических осадков, содержащих платину - Габдурахманова Э. М. Эльвира Маратовна; Горчаков Э. В. Эдуард Владимирович; Глызина Т. С. Татьяна Святославовна; Колпакова Н. А. Нина Александровна (Химия, 2010)
Заглавие с титульного листа